As expectativas e experiências dos cadetes da Força Aérea frente a instituição e ao seu currículo - Souza, Lucy Mary Pinheiro de (1987)
This paper is a confrontation between the expectations of AFA's students and the reality of the curriculum offered by the institution, encompassing both the students' formation and their future professional performance. Among its objectives are: 1) identifying the curricular proposals of the courses offered by the AFA, their respective goals, number of hours, etc.; 2) determining how students and teachers perceive the academic formation and the specific specialized training 3) providing subsidies for a possible curricular reformulation at the AFA.